A Population-Based Evaluation of a Regional Asthma Education Centre - Simone Cowan; Pierre Ernst; André Cartier; Louis-Philippe Boulet (Canadian Respiratory Journal)
BACKGROUND: A population-based, ecological evaluation was conducted to determine the impact of a regional asthma education centre on reducing asthma-related morbidity and improving the quality of prescribing.